Factors Affecting Patient Loyalty of Outpatient of the Social Security Administrator Healthcare - Dea Tansy Ardelia; Arifah Devi Fitriani; Miskah Afriany (Journal La Medihealtico, 2022)
The quality of hospital services is a crucial thing that can be a factor causing patients to be loyal or not. The results of the initial survey found that patients still experience dissatisfaction with the services provided by health workers. The aim of the study was to analyze the factors that influence outpatient BPJS Health Patient Loyalty at Bhayangkara Palembang Hospital in 2021. This quantitative study used a cross-sectional study design which was conducted at Bhayangkara Palembang Hospital which took place from July to August 2021. The study sample was 258 people Accidental sampling . Survey data were analyzed using the Chi Square test and logistic regression. Univariate results showed that the majority of respondents were aged 26-35 years, namely 107 (41.5%) respondents, female, 148 (57.4%) respondents, and had a high school education level, namely 130 (50.4%) ) respondents. Bivariate results There is an effect of image on outpatient Health BPJS Patient Loyalty, there is an effect of comfort on Outpatient Health BPJS Patient Loyalty, there is an effect of service on Outpatient Health BPJS Patient Loyalty, there is an effect of guarantee on Outpatient Health BPJS Patient Loyalty and the variables that have the most influence on Outpatient Health BPJS Patient Loyalty at the Palembang Bhayangkara Hospital in 2021 is a service variable. Suggestions in this study are that the results of this study can be used as input in making policies or standard operating procedures for effective services between health care providers and patients visiting the hospital.